The Impact of Women’s Economic Empowerment on the Rise of Female Entrepreneurship in Namibia - Bobek, Vito; Schachl, Andrea; Horvat, Tatjana (Naše gospodarstvo/Our economy, 2022)
In this paper the authors investigate the importance of women’s economic empowerment and its impact on the rise of female entrepreneurship and human capital in Namibia. The research includes a case study analysis with four in-depth expert interviews. Data triangulation ensure the study’s validity, and the case was examined through pattern matching. The results demonstrate that female entrepreneurs face challenges such as access to resources and education, socio-cultural norms, a lack of social protection, and a large and unprotected informal sector. The government and institutions shall promote women’s empowerment through a direct labour market intervention, support for the informal sector, a gender-sensitive constitutional, legal, and institutional framework, the enforcement and oversight of gender-responsive laws and policies, and access to resources and education. Furthermore, women require digital inclusion, entrepreneur networks, social protection, and reformed socio- cultural norms. If female entrepreneurs are empowered adequately, they will contribute to nations’ human capital, economic growth, and development.